Pendampingan Harmonisasi Keragaman Budaya Dua Negara dalam Peningkatan Sinergisitas Persiapan Pertukaran Pelajar Mahasiswa Internasional - Rafles Ginting; Helma Malini; Nur Fitriana Hamsyi (CAPACITAREA : Jurnal Pengabdian kepada Masyarakat, 2022)
In order to improve the quality of international student exchanges, various related matters must be prepared, also related to cultural harmonization between countries, which of course will determine the synergy and values ​​of unity and solidity among these students, bearing in mind the unification of mindsets and cultural backgrounds of various the state is not a trivial matter, this is what is said to be a phenomenon that must be resolved in order to be able to provide good results in the implementation of the direct learning process between countries on international student learning exchanges which will be held next semester. Given this problem, it is necessary to carry out socialization and assistance regarding the harmonization of the cultures of the two countries (Malaysia and Indonesia) to increase tolerance and synergy in preparation for post-pandemic international student exchanges